2013
DOI: 10.7601/mez.64.73
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal occurrence of larval trombiculid mites by Tullgren's funnel method in Kagoshima Prefecture for three years,with a few references to morphological variations

Abstract: Seasonal occurrence of larval trombiculid mites was surveyed at two adjacent areas using Tullgren s funnel method for three years. Larval trombiculid mites were collected every month from April 2004 to March 2007 at two adjacent areas of Aira City, Kagoshima Prefecture. Twenty trombiculid species were collected from soil samples: Neotrombicula mitamurai, Eltonella ichikawai, Miyatrombicula kochiensis, Cheladonta ikaoensis, Doloisia uchikawai, Helenicula miyagawai, Mackiena todai, Neoschoengastia shiraii, Schou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…6 ). The result is consistent with that in some other provinces of China and some other countries ( Choi et al, 2018 ; Li et al, 1997 ; Liu et al, 2004 ; Noda et al, 2013 ; Park and Shin, 2016 ; Pham et al, 1999 ; Wu et al, 2000 ; Yuan et al, 2003 ). Although the seasonal fluctuation curves of L. ( L. ) scutellare vary in different provinces of China, the basic pattern belongs to the autumn-winter type with the seasonal peak in cold seasons, late autumn and winter ( Bang et al, 2008 ; Elliott et al, 2019 ; Santibáñez et al, 2015 ; Tilak and Kunte, 2019 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…6 ). The result is consistent with that in some other provinces of China and some other countries ( Choi et al, 2018 ; Li et al, 1997 ; Liu et al, 2004 ; Noda et al, 2013 ; Park and Shin, 2016 ; Pham et al, 1999 ; Wu et al, 2000 ; Yuan et al, 2003 ). Although the seasonal fluctuation curves of L. ( L. ) scutellare vary in different provinces of China, the basic pattern belongs to the autumn-winter type with the seasonal peak in cold seasons, late autumn and winter ( Bang et al, 2008 ; Elliott et al, 2019 ; Santibáñez et al, 2015 ; Tilak and Kunte, 2019 ).…”
Section: Discussionsupporting
confidence: 90%
“…The five main chigger species had their own seasonal fluctuation patterns. Before the present study, some previous investigations had reported the seasonal fluctuations of L. ( L. ) deliense , L. ( L. ) scutellare and A. indica in some other provinces of China and some other countries ( Frances et al, 1999 ; Kim et al, 2019 ; Li et al, 1997 ; Noda et al, 1996 , 2013 ; Wu et al, 2013 ), but no literature was on the seasonal fluctuations of W. ( W. ) micropelta and W. ( W. ) turmalis . In the present study, the Cr , MA and MI of W. ( W. ) micropelta were relatively high from March to July with a slight peak in May and the mite had an irregular seasonal fluctuation without an obvious peak ( Fig.…”
Section: Discussionmentioning
confidence: 68%